(untitled) (Informatica, 2022)
An approach to eliminate multicollinearity problems in regression analysis using QR decomposition of rectangular matrices by Householder reflection has been proposed. The reliability of this computational procedure has been proved. Povzetek: Predložen je pristup uklanjanju problema multikolinearnosti u regresijskoj analizi korištenjem QR dekompozicije pravokutnih matrica Householderovom refleksijom. Dokazana je pouzdanost ovog proračunskog postupka.